A family of von Hippel-Lindau disease with renal cell carcinoma--case report and review of the literature - Ito, F (Hinyokika kiyo. Acta urologica Japonica, 1991)
We report a 63-year-old woman with renal cell carcinoma associated with von Hippel-Lindau disease. The patient was referred to the department of neurosurgery at our hospital, complaining of gait disturbance. There was a history of retinal hemangioma. After further examination, von Hippel-Lindau disease was the conclusion with evidence of cerebellar hemangioblastoma. An abdominal CT-scan and arteriography revealed multiple hypervascular tumors in the right kidney, but not in the left. She underwent a right radical nephrectomy and lymphadenectomy 2 months after resection of a brain tumor. Von Hippel-Lindau disease is generally recognized as an autosomal-dominant inherited disorder. The patient had a positive family history, seen in both her younger brother and son. Both were diagnosed with renal cell carcinoma with central nervous system involvement before any sign of disease was found in the patient. Twenty one cases of von Hippel-Lindau disease associated with renal tumors have been reported in the Japanese literature. The clinical findings of these cases are discussed